A review on molten salt synthesis of metal oxide nanomaterials: Status, opportunity, and challenge. (April 2021) - Gupta, Santosh K.; Mao, Yuanbing
Abstract: Molten-salt synthesis (MSS) method becomes an excellent bottom-up synthesis technique of nanomaterials with various chemical compositions and morphologies because of its meritorious features including environmental friendliness, low cost, simple to operate, easy to scale-up, etc. This review article highlights the status, potential and challenges of MSS for the synthesis of metal oxide nanomaterials. It gives a concise flavour on the importance of synthesis on the properties and application of nanomaterials. We have compiled a brief write-up on a few frequently used synthesis methods and their advantages and disadvantages. This review article encompasses different aspects of MSS such as the role of molten salt, the choice of molten salt, the effect of various synthesis parameters, typical oxosalts and their electrochemical aspects. Some advanced modifications of the MSS method and their implications are also discussed in brief citing a few examples. For readers to have a completed understanding and feel of MSS, both pros and cons of it have been discussed as well. The recent progress in MSS of inorganic metal oxide nanoparticles is reviewed in this article. We start with simple binary oxides and then explain a few technologically important cases of complex metal oxide nanomaterials. This review article also highlights how the MSS method has been successful in synthesizing ABO2 delafossite, ABO3 perovskite, AB2 O4 spinel and A2 B2 O7 pyrochlore nanomaterials. This review article opens a new avenue for exploring MSS in making size and shape tunable nanomaterials for various catalytic, optoelectronic, magnetic, and electrical applications.